Guidance on Modernizing Statistical Legislation - United Nations Department of Economic; Social Affairs (United Nations, 2019)
The Guidance on Modernizing Statistical Legislation aims to support and inspire countries wishing to benchmark or update the legal framework of their national statistical systems. Based on a review of the current legal and institutional frameworks and the operational environment of statistical production, the Guidance identifies common elements of statistical legislation and their intended outcomes as well as emerging issues relevant for statistical legislation. The Guidance builds on the Generic Law on Official Statistics developed by UNECE for the countries of Eastern Europe, Caucasus and Central Asia and is aligned to the Fundamental Principles of Official Statistics, the European Statistics Code of Practice and the OECD Recommendation on Good Statistical Practice.